Diseño de lineamientos estratégicos y comunicación digital para el posicionamiento institucional de la Universidad Estatal del Sur de Manabí. - Parrales Poveda, María Leonor (2014)
Establish a plan of strategic guidelines based on digital communications to improve the institutional position of the State University of Southern Manabí UNESUM, is of vital importance given the current situation of the institution; It is on this premise that the thesis is oriented and concrete through a process of research, both literature and field. In Chapter II a contextualization of UNESUM especially related to the new legislation on higher education and regulations, as well as instruments that defined the institution of facing the intervention process that is currently defined above. In Chapter III the current situation of the State University of Southern Manabi from the perspective of the strategic guidelines and digital communication is diagnosed, including the key components of quality and academic excellence are CEAACES assessment parameters, and also the result of the degree of acceptance of the university community related thesis topic unfolds. The study concludes with a proposal for strategic guidelines and digital communications to improve the position of the State University of Southern Manabí.